2018
DOI: 10.9735/0975-5276.10.3.1058-1061
|View full text |Cite
|
Sign up to set email alerts
|

SUGARS MEDIATED GERMINATION IN SPORES OF Bacillus megaterium

Abstract: Research project: 'Spore based sensor for pesticide residues in milk'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this regard, it was earlier demonstrated that the difference in outgrowth time of two single spores is proportional to their difference in germination time. Depending on the nutrient of the germination medium or the origin of spores, germination times can vary considerably [17,18]. These differences explain why colonies from outgrowth of spores in a population appear at different times during incubation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it was earlier demonstrated that the difference in outgrowth time of two single spores is proportional to their difference in germination time. Depending on the nutrient of the germination medium or the origin of spores, germination times can vary considerably [17,18]. These differences explain why colonies from outgrowth of spores in a population appear at different times during incubation.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34] Bacterial spores are robust, vegetative, and metabolically dormant, and are produced to survive the severe and adverse climatic conditions of starvation and stress. 132,133 Exposure to germinants induces the germination of spores, which are highly resistant to varying ranges of temperature, pressure, desiccation, ultraviolet radiation, pH extremes, and noxious chemicals, including hypochlorite, aldehydes, ethylene oxide, and several other extreme conditions. 132,134 In the presence of specific small molecule germinants such as L-Ala or other nutrients, spores interact via germinant-specific receptors to reactivate their metabolism and allow for vegetative growth in Bacillus spp.…”
Section: Prokaryote Production Of D-aasmentioning
confidence: 99%